Me belisque real! corpo objeto, corpo sujeito e os limites superficiais de suas interfaces nas pós-humanidades de Sob a pele - Madeiros, Jose Eider (2024)
This research aims to analyze the interfaces of the skin as a semi-sign, as an allegory and as a representational topological surface, in concepts of the body incited by two homonymous works entitled Under the skin, by Michel Faber, in literature, on the one hand, and translated by Jonathan Glazer, for cinema, on the other, and that allow a dialogue with Freudolacanian psychoanalysis. In view of the critical developments of contemporary reality, around issues that are dedicated to con-tactile relations in the post-modernity and post-humanity horizons, the body and its touching surface are crossed by countless problems and difficulties. This occurs when dealing with phenomena of subjectivity in relation to the other, the perceptions of oneself in relation to this other, and the limits that give consistency or not to intimate aspects of suffering or loneliness, resulting from ambivalence, at the same time internal and external, of the subject in the clinical dimensions of desire and proprioception. The research questions, as it focuses on the feminine as a creature and alien creation featured in the works, about how a reading from the perspective of science fiction can launch reflections that expand the functions of the body's skin in an aesthetic allusion to the challenges of human time and place in relation to present reality. In this sense, when considering the implications of some theoretical gaps in the psychoanalytic field, the research launches a hypothesis around the haptic drive, according to what is arranged in its dialogical and methodological path, especially when faced with possibilities for configuring sensoriality modulations to other forms of corporeality, typical of technological advances and fictions in progress through contemporary times. Regarding theoretical articulations for the axis of an aesthetic analysis, the research is most inspired by the visions of fragmentation in Walter Benjamin and criticism in Georg Lukács and Fredric Jameson, and for the axis of psychoanalysis, in the various texts of Sigmund Freud and Jacques Lacan, which are focused on body models of the psychic surface and the rupture of these models by structural topology. In the brief passages through the axes between psychosomatics and the previous others, the works of Didier Anzieu and Christophe Dejours serve as an important parameter for this research. The theoretical assumptions focused on science fiction and cinematographic language come from different authors. It will be understood, within the limits imposed on literary-filmic analysis, that the heroines are de-monst(e)rations, as creatures, of the impossible body of symptom in complex positions to that which persists towards non-ex-istence and to uncanniness of the events in space-time of postmodern human fictions, which are experienced at levels of paradoxical resistance and permanence in superficiality, fundamental to the constant, violent and cyclical crisis of post-human speak-being.